2015
DOI: 10.1128/ec.00043-15
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Function of the Response Regulator BcSkn7 in the Stress Signaling Network of Botrytis cinerea

Abstract: Important for the lifestyle and survival of every organism is the ability to respond to changing environmental conditions. The necrotrophic plant pathogen Botrytis cinerea triggers an oxidative burst in the course of plant infection and therefore needs efficient signal transduction to cope with this stress. The factors involved in this process and their precise roles are still not well known. Here, we show that the transcription factor Bap1 and the response regulator (RR) B. cinerea Skn7 (BcSkn7) are two key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…Production of reactive oxygen species (ROS) by fungal strains was assayed according to Viefhues et al (2015) with minor modifications. Briefly, YGG-agar solid medium was overlaid with cellophane, inoculated with mycelium plugs, incubated for 4 days, and finally used to harvest 6 mg of fresh mycelium that was then placed at the bottom of a well in a microtiter (96 wells) plate.…”
Section: Materials and Methdosmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of reactive oxygen species (ROS) by fungal strains was assayed according to Viefhues et al (2015) with minor modifications. Briefly, YGG-agar solid medium was overlaid with cellophane, inoculated with mycelium plugs, incubated for 4 days, and finally used to harvest 6 mg of fresh mycelium that was then placed at the bottom of a well in a microtiter (96 wells) plate.…”
Section: Materials and Methdosmentioning
confidence: 99%
“…Then 250 μl of a 3,3′-Diaminobenzidine (DAB) solution (0.5 mg/ml DAB in 100 mM citric acid, pH 3.7) were added to cover the mycelium, and the plate was incubated for 1.5 h in the dark and visually evaluated. Positive and negative controls were done as in Viefhues et al (2015). Production of ROS during infection was assayed in tobacco leaves inoculated with 5-μl droplets of a conidial suspension (5 × 10 5 conidia/ml in TGGK solution).…”
Section: Materials and Methdosmentioning
confidence: 99%
“…It is widely believed that the dark pigmentation of conidia and sclerotia is due to the accumulation of DHN melanin (Zeun and Buchenauer, 1985;Bell and Wheeler, 1986;Doss et al, 2003). Mutants producing increased amounts of a dark pigment and expression studies of some predicted melanogenic genes have been described (Schamber et al, 2010;Liu et al, 2011;2013;Yang et al, 2013;Viefhues et al, 2015); however, the involvement of the analyzed genes in melanogenesis was not shown. Recently, Zhang et al (2015) reported on two genes required for conidial melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bap1 and BcSkn7 share several target genes, including Bctrx1 , Bctrr1 , Bcgpx3 , and Bcgrx1 and thus a coordinated regulation of Bap1 and BcSkn7 is possible. Nevertheless, the role of BcSkn7 in pathogenicity is only minor (Yang et al 2014 ;Viefhues et al 2015 ). Besides the previously mentioned transcription factors, the Cys2His2 zinc fi nger protein Msn2/4 could play a role in ROS response in concert with Bap1 and Skn7.…”
Section: Transcriptional Regulation Of Osr Genesmentioning
confidence: 96%
“…Glutathione peroxidase for example can convert H 2 O 2 to H 2 O upon oxidation of glutathione. However, investigations of the glutathione peroxidase BcGpx3 showed neither involvement in pathogenicity nor in response to oxidative stress (Viefhues et al 2015 ). Because of the numerous ROS detoxifying enzymes, the effect of a single deletion can be masked in most cases.…”
Section: Other Ros Detoxifying Enzymesmentioning
confidence: 99%